Two sexually compatible monokaryons from a heterokaryotic Lentinula edodes strain respond differently to heat stress - Guo, Yuan; Jiao, Wenyu; Zhang, Yajie; Tan, Meiting; Gao, Qi; Liu, Yu; Wang, Shouxian (Frontiers in Microbiology, 2025)
BackgroundDespite the extensive research conducted on heat responses of Lentinula edodes heterokaryotic cells, the responses of the two sexually compatible monokaryons to heat stress (HS) remain largely unknown.MethodsTo bridge this gap, we examined the nucleus-specific (SP3 and SP30) heat resistant mechanisms using an integrated physiological, metabolomic and transcriptomic approach.ResultsThe results showed that HS elicited the boost of ROS and hampered mycelium growth for both monokaryons. Metabolome and transcriptome analysis demonstrated that the two sexually compatible monokaryons responded differently to HS. For SP3, the differentially expressed genes (DEGs) were significantly enriched in Mitogen-Activated Protein Kinase (MAPK) signaling, cell cycle and sugar metabolism, whereas those DEGs for SP30 were enriched in glyoxylate and dicarboxylate metabolism, and protein processing. The differentially accumulated metabolites (DAMs) of both strains were enriched in the glycerophospholipid metabolism, alpha-linolenic acid metabolism, biosynthesis of cofactors, etc, but were regulated differently in each strain. The enriched KEGG pathways for SP3 tend to be downregulated, whereas those in SP30 exhibited a contrary trend. The genes in MAPK signaling pathway were associated with the glycerophospholipid metabolism in SP3, but not in SP30. Omics-integration analysis revealed distinguishing regulatory networks and identified completely different hub genes for the two strains.DiscussionOur findings revealed, for the first time, the different heat-resistance mechanisms of the two compatible nuclei and provided candidate metabolites, responsive genes and regulatory pathways for further experimental validation.